The Use of Superlingo Application to Improve Students’ Pronunciation Skills - Husna, Asmaul; Lubis, Yani (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to evaluate the effectiveness of the Superlingo application in enhancing junior high school students' English pronunciation skills. Pronunciation mastery is a crucial aspect of English language learning, yet it often poses challenges for students due to limited practice time and conventional teaching methods. This research employed a mixed-methods approach, combining a quantitative experimental design (pre-test and post-test) with a qualitative phenomenological approach through in-depth interviews. A total of 30 eighth-grade students were selected and divided into two groups: an experimental group using the Superlingo application and a control group applying traditional learning methods. The quantitative results revealed that the experimental group showed a significant average score improvement of 7.2 points (from 18.4 to 25.6), while the control group improved by only 2.2 points (from 18.1 to 20.3). A paired sample t-test confirmed the statistical significance of the improvement (p < 0.05). Meanwhile, qualitative findings indicated that features such as AI-powered speech recognition, gamification, and interactive exercises boosted students' learning motivation and confidence in speaking English. However, challenges such as internet connectivity and occasional AI misjudgment of pronunciation accuracy were also reported. These findings suggest that integrating AI-based applications like Superlingo into the curriculum can significantly enhance pronunciation learning. This study contributes to the development of modern, adaptive, and student-centered digital learning strategies.